Training on the Implementation of the Halal Product Assurance System for Micro and Small Enterprises to Increase Their Intention to Obtain Halal Certification - Layung Anindya Prasetyanti; Netti Siska Nurhayati; Eka Surachman; Mokh Adib Sultan Sari; Maya Sari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The Administrative District of Kepulauan Seribu, despite being located within the Special Capital Region (DKI) of Jakarta, has a lagging economy compared to other administrative regions of Jakarta. In fact, Kepulauan Seribu has significant development potential, particularly in tourism, fisheries, and food processing. Currently, 90% of businesses in Kepulauan Seribu are Micro, Small, and Medium Enterprises (MSMEs). These enterprises have significant potential to grow in line with the region’s own resources and opportunities. On the other hand, the national administration has mandated halal certification for food and beverage products, effective October 17, 2024. This requirement will also extend to MSMEs’ food and beverage products, effective from October 17, 2026. Furthermore, the government, through the Ministry of Tourism, is actively promoting halal tourism, aiming to position Indonesia as a global leader in the sector. Therefore, training on the Halal Product Assurance System is considered essential to strengthen the economy of Kepulauan Seribu by preparing its MSMEs to register for halal certification. Following Ajzen’s Theory of Planned Behavior, the training emphasized positive attitudes and subjective norms and aimed to lower perceived behavioral control. The study shows that the training led to a high intention to apply for halal certification.